MANAJEMEN RANTAI PASOK PADA INDUSTRI KECIL MENENGAH GARAM MADURA DENGAN PENDEKATAN HOUSE OF RISK - Trisita Novianti; Issa Dyah Utami; Samsul Amar (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2025)
Madura Island is recognized as a primary salt supplier in Indonesia, contributing significantly to national production. Despite this, its Small and Medium Enterprises (SMEs) face persistent challenges that create a precarious supply chain, characterized by noncompetitive pricing and extended, inefficient distribution networks. These vulnerabilities necessitate a structured approach to risk management. Therefore, this study aims to identify dominant supply chain risks, analyze their root causes, and formulate effective mitigation strategies for Madura salt SMEs. The methodology employs a two-stage approach. First, the Supply Chain Operation Reference (SCOR) model is used to map processes and identify potential risk events. Second, the House of Risk (HOR) model is applied. HOR Phase 1 prioritizes the risk agents based on their severity and occurrence, and HOR Phase 2 develops proactive mitigation actions. The research identified 9 distinct risk events and 23 corresponding risk agents across the SCOR processes. The HOR 1 analysis revealed that the most critical risk agents are insufficient solar heat intensity (A9), high precipitation (A10), price manipulation by intermediaries (A4), and inadequate salt processing competence (A11). From these priorities, seven strategic mitigation actions were formulated in HOR 2. The most crucial recommendations include implementing solar heat monitoring technology, developing contractual partnerships to stabilize prices, and providing technical training for farmers on salt processing standards. This research provides actionable strategies to enhance the overall resilience and sustainability of the salt SME supply chain.